Maulana Altaf Hussain Hali's Arabic Letters A Review and Contemporary Guidance on Urdu Translations (Al-Aasar, 2025)
Maulana Altaf Hussain Hali was a renowned poet, prose writer and writer of Urdulanguage and literature. Along with Urdu, he was proficient in Arabic and Persianlanguages. These seven letters of his are a fine example of Arabic prose. They usefluent Arabic language, however, many errors of writing have come to light in them,which have been corrected as much as possible, however, these errors have notbeen pointed out so that the continuity of these letters is not affected. The translationof these letters has not been faithful to the words, but the meaning has beenpresented in a concise manner. For example, surah Yousaf: 88 the translation of theverse in the first letter is as follows: “We have been besieged by calamities from allsides, so help us. And fill our empty cups.” Although this is not a translation of theverse but a claim, the translation of the verse is as follows: “O my beloved! We andour families have been afflicted and we have brought a small fortune, so give us fullmeasure and give us charity. Indeed, Allah rewards those who give charity.” Thetranslation of the supplications at the beginning and end of these books has alsobeen omitted, or they have been mentioned explicitly in the translation (without theUrdu translation).